MEMBONGKAR KESALAHAN POLA ASUH ANAK DALAM MITOS-MITOS DI INDONESIA - Liliani, Else (Diksi, 2015)
This article is about a research conducted to clarify (1) the structural characteristics of myths in Indonesia, (2) the child-rearing patterns found in the myths, (3) errors in child rearing reflected in the myths, and (4) the relevance of the myths and child-rearing patterns to the contemporary realities in Indonesia. With the myths in Indonesia as the objects of the research, by means of purposive random sampling, 15 myths were selected for study. The data were obtained by means of a read-and-write technique and they were analyzed by (1) reading the myths and seeking the story units and (2) organizing the story units in accordance with the story development. The validity of the data was tested through semantic validity and their reliability was tested by repeated readings. The research results indicate that (1) the structural characteristics of myths in Indonesia are, among others, that (a) in child rearing the mother figures have the characteristic of being gentle and a part of the father figures have the characteristic of being stern, (b) most of the myths have the social background of the lower class and the economic background of the poor, (c) the child figures possess a sufficiently good need of achievement and a sufficiently good emotional quotient, (d) the child figures experience considerable social conflict, (e) the parent figures play minimum parts in the story, and (f) most of the child figures receive punishments and experience dehumanization, (2) the patterns of child rearing are found to have enough variety but they are mostly dominated by authoritarian, neglectful, and indulgent ones, (3) the errors of child rearing reflected are, among others, the minimum roles of parents and a disproportional child-rearing pattern of giving more punishments than rewards, and (4) the myths put under study have relevance to today's matters related to child rearing such as education, health, and child abuse. Keywords: myths, structure and pattern of child rearing